2021
DOI: 10.1093/bjs/znab301
|View full text |Cite
|
Sign up to set email alerts
|

Drug-coated balloon angioplasty for failing haemodialysis access: meta-analysis of randomized clinical trials

Abstract: Background Arteriovenous fistulas, a major treatment for end-stage kidney disease, frequently require endovascular reinterventions to maintain haemodialysis function. Drug-coated angioplasty balloons (DCBs) were developed with the intention of reducing reintervention rates. The aim of this study was to perform a systematic review and meta-analysis of DCBs in the treatment of failing haemodialysis access. Methods Electronic da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 40 publications
1
6
0
Order By: Relevance
“…Four studies investigating the effect of DEB (21)(22)(23)(24) and nine studies investigating the effect of DCB were included in our NMA (12,(15)(16)(17)(18)(19)(20)(21)29). The results demonstrated that both DEB and DCB had a statistically higher patency rate compared with PBA at all time points, which was consistent with the results of several recently published studies (40,41). Meanwhile, both these studies demonstrated that the use of DCB did not cause a significant increase in patient mortality, indicating the high safety of DCB compared with PBA.…”
Section: Discussionsupporting
confidence: 86%
“…Four studies investigating the effect of DEB (21)(22)(23)(24) and nine studies investigating the effect of DCB were included in our NMA (12,(15)(16)(17)(18)(19)(20)(21)29). The results demonstrated that both DEB and DCB had a statistically higher patency rate compared with PBA at all time points, which was consistent with the results of several recently published studies (40,41). Meanwhile, both these studies demonstrated that the use of DCB did not cause a significant increase in patient mortality, indicating the high safety of DCB compared with PBA.…”
Section: Discussionsupporting
confidence: 86%
“…There have been recent meta-analyses that pool results of multiple randomized control trials (RCTs) that assess outcomes of stand-alone PTA to treat dysfunctional AV access. 6,[19][20][21][22] Ng et al reviewed seven studies that reported a cumulative 1147 subjects (867 AVGs, 280 AVFs) with a range of target lesion patency at 6 months of 8%-34% for subjects treated with PTA. 20 Liao et al conducted a meta-analysis of 11 RCTs PTA in AVF that pooled 976 subjects and reported 6-month patency of 51.7% (236/489) for a PTA cohort.…”
Section: Discussionmentioning
confidence: 99%
“…6 A study by Hu et al conducted a meta-analysis of 18 RCTs of DCB versus PTA in AVF that pooled 1898 subjects with the PTA cohort associated with a 6-month primary patency of 58.6% (499/851). 21 Supporting Information Table S1 summarizes the literature comparison results. 6,[20][21][22][23] The observation of comparable target lesion primary patency in the FLEX-AV registry relate to those reported by RCTs is remarkable given that inclusion criteria for RCTs are more stringent than those for this allcomers registry.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations